The relationship between working environment and job satisfaction among public sector employees at Community Development Department (KEMAS) Kota Samarahan, Sarawak / Nur Fadhilah Radzuan - Radzuan, Nur Fadhilah (2018)
The working environment has a huge impact towards employee's job satisfaction. The variables included in working environment are top management and esteem needs, job safety, security and working hours, and relationship with co-workers. The objective of this study is to investigate the relationship between working environment and job satisfaction among public sector employees at Community Development Department (KEMAS) Kota Samarahan, Sarawak. Data was collected through questionnaire and the questionnaire was adapted from a previously validated survey. Convenience sampling was used for collecting data from 108 in Community Development Department (KEMAS) Kota Samarahan, Sarawak. The result shows a positive and strong relationship between working environment and employee job satisfaction in Community Development Department (KEMAS) Kota Samarahan, Sarawak. Hence, some recommendations for organization, employees and future researchers had been highlighted in this study.